Ab initio investigation of the role of charge transfer in the adsorption properties of H2, N2, O2, CO, NO, CO2, NO2, and CH4 on the van der Waals layered Sn3 O4 semiconductor AB INITIO INVESTIGATION of the ROLE ... FREIRE, ORLANDI, and da SILVA - Freire, Rafael L. H.; Orlandi, Marcelo O. [UNESP]; Da Silva, Juarez L. F. (American Physical Society (APS), 2020)
We report an atomistic investigation, based on density functional theory calculations within the D3 van der Waals correction, of the adsorption properties of H2, N2, O2, CO, NO, CO2, NO2, and CH4 on the semiconductor Sn3O4(010) monolayer surface. Except for NO2 and NO molecules, the adsorption energies are from -64meV (H2) up to -167meV (CO2) with the molecule-surface distances larger than 3.30Å for all molecules, and hence, minor effects were observed on the Sn3O4(010) surface electronic structure upon adsorption. NO2 has the largest adsorption energy (-525meV), which can be explained by closer approach of the two O atoms towards the surface, while NO binds to the surface with about half of the NO2 adsorption energy (e.g., -279meV). From Bader analysis, we found substantial charge transfer from the surface to the molecules, -0.52e (NO2) and -0.23e (NO), which is consistent with the smaller distances to the surface, 2.46 and 2.82Å, respectively. Thus, those results suggest an improved detection performance of Sn3O4 towards NO2, which can help to design sensor devices based on the Sn3O4(010) monolayers.